Melatih Keterampilan Literasi Sains Mahasiswa Melalui Uji Kualitas Mikrobiologi Menggunakan Metode Perhitungan Angka Total - Ferry Irawan; Harahap, Dharma Gyta Sari; Muh. Rafi'y (Yayasan Perguruan Kampus, 2023)
Food was consumed in everyday life. Various and derivation types of processed products that we consume are obtained from industrialized products that are oriented towards the processing of the food industry. Processed food products in the form of fish that go through various kinds of management can be contaminated with thermal temperatures and bacteriophages which are parasitic and have a negative impact on health. The research carried out aims to test the quality of microbes contained in fish that have been preserved using various types of preservatives. This research procedure uses the Standard Plate Count (ALT) technique which can provide a representative test for the types of microbes found in cured tilapia fish at certain time intervals. The results of the research data were analyzed using the ANOVA test which consisted of 5 repetitions, this was aimed at determining the average distribution of each repetition of the research procedures carried out showing coherent results. The results showed that the ALT sampling technique was effective in determining colonies of bacteriophages and other micro-organisms (pathogenic microorganisms) present in preserved tilapia fish that could differentiate into viruses that are harmful to public health.